Impact of E-Commerce and Accounting Information Systems on Entrepreneurship Decisions: A Case Study of Accounting Students at UPNVJT - Mauluddyah, Diva Ayu Rahma; Munari, Munari (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study examines the role of E-Commerce and Accounting Information Systems (AIS) in encouraging entrepreneurial decisions among students at UPNVJT. Methodology: A literature review method was used, drawing from articles accessed via the Publish or Perish 8 application, with keywords such as e-commerce, AIS, entrepreneurship, and entrepreneurial interest. Results: The study finds that while e-commerce alone does not significantly influence entrepreneurial decisions, AIS does. The combined effect of AIS and e-commerce has a significant impact on entrepreneurial decision-making. Findings: Technological knowledge and intrinsic motivation significantly influence students' entrepreneurial choices. Novelty: The impact of accounting information systems and e-commerce on students' entrepreneurial choices is examined in this study. This study uniquely integrates the roles of e-commerce and AIS in shaping entrepreneurial decisions, with a specific focus on UPNVJT accounting students. Originality: Unlike prior research, this study uses SPSS analysis and a specific focus on accounting students to assess the impact of these technologies on entrepreneurial intentions. Conclusion: While e-commerce alone has minimal impact, integrating AIS for financial management and e-commerce for marketing can provide students with the necessary tools to pursue entrepreneurship. Type of Paper: Research Paper